Pengelolaan Program Pekarangan Pangan Lestari Melalui Kelompok Wanita Tani di Kelurahan Pematang Kapau Kecamatan Kulim Kota Pekanbaru - Nilanda Rizky; Dadang Mashur (Jurnal Ilmiah Wahana Pendidikan, 2022)
The Sustainable Food Garden Program (P2L) is a service program as an economic development effort to reduce malnutrition rates in Pematang Kapau Village. This program is here to take action against food insecurity, priority stunting interventions, or to take action on priority areas for food insecurity and to strengthen food security areas. This study aims to find out how good management is in the Sustainable Food Garden Program through the Cendana Wangi Farmer's Women's Group in Pematang Kapau Village. The theoretical concept that the researcher uses is the theory of George R. Terry. Good management has 4 functions, namely the term POAC, which stands for Planning, Organizing, Actuating, and Controlling. The study used qualitative research methods, with data collection techniques based on interviews, observations and documentation. The results of the research found that the management of the Sustainable Pangan Yard Program was going well, however. This has two possibilities, it can have a positive impact and it can also have a negative impact, depending on how KWT manages benefits. The positive is that participants can be independent and can decide stunting rates and the negative is that KWT only enjoy temporary assistance without any economic improvement around the community. Factors that affect program management are the lack of participation of group members in the program implementation process and inadequate facilities and infrastructure provided in the program. the management of the Sustainable Food Garden (P2L) program so that it is not optimal.